Analisis Kelembagaan Pola Penggunaan Lahan Kawasan Hutan Lindung di Kawasan Bandung Utara (KBU), Kabupaten Bandung - Bagus Budiprakoso; Iin Ichwandi; Omo Rusdiana (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Land use degradation has always been a problem for forest areas. Numerous past studies have investigated that there are patterns in the forest area's land use management that support forest sustainability and society's economy. This research aims to identify the action arena and patterns of interaction, to describe the outcomes of the two land use patterns, and to formulate the strategy related to forest area land use pattern in North Bandung Area, Bandung Regency. This research used Institutional analysis and development (IAD) framework as the research method. The identified action arena includes the pattern of commodity and profession transfer. The actors involved were State-owned Forest Enterprises (Perum Perhutani), Village Administrations, forest extensions, Forest Village Community Association (FVCA), and Forest and Farm Producers Organization (FFPO). The most dominating actor in land use activities in both patterns was Perum Perhutani, along with FVCA and FFPO. The pattern of interaction that exists between actors was prospering with only minor problems found within its coordination system. The outcome of the application of these two patterns, among others, is to raise public awareness in conserving forests and improving the community's economy. The land management strategy for forest areas can be directed using the Penta helix concept.